Efek Penambahan Aditif Golongan Karboksilat dalam Menghambat Laju Pembentukan Endapan Kalsium Sulfat - Suharso, Suharso; Buhani, Buhani (Jurnal Natur Indonesia, 2011)
Scale formation is a serious problem encountered in many industries including oil or gas production, watertransport, power generation and batch precipitation. Several additives used have been known to inhibit scaleformation. This method is used because it is cheaper and effective in inhibiting scale formation. At this research,it was invesigated the effect of additional additive from carboxyl groups like citric acid, oxalate acid, and benzoicacid as inhibitor of kalsium sulfate (CaSO4) scale formation using conductivity method at temperature of 400C. Theresult showes that additives used are able to inhibit kalsium sulfate (CaSO4) scale formation under this condition.